Peningkatan Value Added dalam Industri Tahu melalui Penerapan Lean Manufacturing dan Analisis Waste - Fredy Sumasto; Muhammad Raihan Akbar; Shafiratul Fajri Harisul Husna; Indra Rizki Pratama; Isma Wulansari; Muhamad Fahrul Rozi; Ahlan Ismono (Jurnal Serambi Engineering, 2023)
Productivity is the most vital part of the food industry as it is one of the priority industries in Indonesia. PD. Saluyo is an industry that produces tofu, which needs to increase production efficiency to meet market needs. The problem in the tofu production process is the high waiting time during soybean soaking. The approach used in this research is lean manufacturing by mapping the process using Value Stream Mapping so that Value Added, Non-Value Added and Necessary Non-Value Added activities can be mapped. Further, Value Added, Non-Value Added and Necessary Non-Value Added data processing is weighted in VALSAT to determine the most significant waste and mapped through PAM. The mapping results obtained a VA of 3,29%, NVA of 90,64% and Necessary Non-Value Added of 6,06%. Based on the results of the VALSAT calculation, the most significant waste is found in time waiting and unnecessary motion. These results are re-mapped in PAM for further analysis using the Cause-Effect Diagram. The analysis results of PAM and the Cause-and-Effect Diagram proposed improvements to change the soaking process method using hot water and create a new SOP to adjust to the proposed production process. The results of the proposed improvements can increase the value added by 0,07% from 3,29% to 3,36%.